Effect of Rice Based Distiller Dried Grain Solubles (Rddgs) With or Without Enzyme Supplementation on Performance And Biochemical Parameters on Commercial Layer Chickenâ€ - ., Shirisha; Lakshmi, Vijaya; Krishna, Daida; Kumari, Nalini; Raju, M.V.L.N. (Indian Journal of Animal Nutrition, 2022)
The objective of this study was to evaluate the Effect of Rice Based Distiller Dried Grain Solubles (RDDGS) with or without Enzyme Supplementation on Commercial layer chicken. Two hundred forty commercial layer chickens at 26 weeks age were randomly allotted to 10 treatments each treatment containing 6 replicates and 4 layers in each replicate. A standard layer ration (CP 18%, ME 2600 kcal/kg diet) was offered to birds. Cocktail Enzyme supplemented @ 250gm/ton of feed. The feed and water were provided adlib during the entire experimental period (4 periods of each 28 days from 27 to 42 weeks). The birds were raised in cages under uniform management and fed the respective diets from 27th to 42nd weeks of age. Â Authors concluded that 15%RDDGS with enzyme supplementation was more effective among all the dietary treatments in terms of performance and serum biochemical variables in White Leghorn (WL) layerÂ Â during the entire experimental period.